2014
DOI: 10.1002/dta.1668
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel and potentially lethal designer drug (±)‐cis‐para‐methyl‐4‐methylaminorex (4,4'‐DMAR, or ‘Serotoni’)

Abstract: During the second half of 2013, a total of 26 deaths involving para-methyl-4-methylaminorex (4,4’-DMAR) were reported to the European Monitoring Centre for Drugs and Drug Addiction. While aminorex and 4-methylaminorex (4-MAR) are known psychostimulants, nothing is known about the comparatively new para-methyl analogue. Analytical characterization of two independent samples obtained from online vendors confirmed the presence of the (±)-cis isomer that also appeared to be involved in at least 18 of the 26 deaths… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(85 citation statements)
references
References 30 publications
(72 reference statements)
5
79
1
Order By: Relevance
“…This effect resembled those previously observed with amphetamine and its analogs, such as phenethylamines/3,4-methylenedioxymethamphetamine--like drugs (Wellman et al, 2009;Pálení cek et al, 2011;López-Arnau et al, 2012;Aarde et al, 2013;Miliano et al, 2016), and is very likely attributable to the fact that cis-4,49-DMAR induces the release of biologic monoamines, particularly dopamine (Charntikov et al, 2011;Brandt et al, 2014;McLaughlin et al, 2015). The rapid appearance and rapid decline of this behavioral effect is consistent with the PK profile of the compound in the brain, although a delay of about 1 hour could be noted (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 83%
“…This effect resembled those previously observed with amphetamine and its analogs, such as phenethylamines/3,4-methylenedioxymethamphetamine--like drugs (Wellman et al, 2009;Pálení cek et al, 2011;López-Arnau et al, 2012;Aarde et al, 2013;Miliano et al, 2016), and is very likely attributable to the fact that cis-4,49-DMAR induces the release of biologic monoamines, particularly dopamine (Charntikov et al, 2011;Brandt et al, 2014;McLaughlin et al, 2015). The rapid appearance and rapid decline of this behavioral effect is consistent with the PK profile of the compound in the brain, although a delay of about 1 hour could be noted (Supplemental Fig.…”
Section: Discussionsupporting
confidence: 83%
“…A study carried out recently involving the characterization of 4,4′-DMAR obtained from online vendors and case samples revealed the presence of cis -4,4′-DMAR. [2,5] …”
Section: Introductionmentioning
confidence: 99%
“…Similar to the aminorex analogs previously detected on the NPS market, [20,21] the fluorinated analogs of phenmetrazine contain two chiral centres which yield the potential for four stereoisomers and two racemic mixtures (i.e., cisand trans-racemates) ( Figure 1C). The results observed for the preparation of the FPM isomers were consistent with the reported synthesis of phenmetrazine where the formation of the more trans-isomer was reported.…”
Section: Of the Fluoropropiophenone Starting Materials (A) Yielding αmentioning
confidence: 71%
“…Similar to that of other anorectic agents such as aminorex, [20,21] the chemical structure of phenmetrazine may be open to structural manipulation through Figure 1A) were synthesized and pharmacological evaluations revealed that both isomers were substrate-type monoamine releasers with higher selectivity toward catecholamines. [3] In the synaptosomal preparations used, 3-FPM showed higher potency than 4-FPM in the ability to induce dopamine and norepinephrine release and further investigations related to the 2-FPM isomer are needed for further comparisons.…”
Section: Introductionmentioning
confidence: 99%